PENYULUHAN RESIKO JATUH PADA LANSIA DI MASYARAKAT KEC. SIANTAR MARTOBA - I Ngurah Gede Verar Fujastawan; Rodearni Damanik (Nusantara Hasana Journal, 2024)
This study discusses the risk of falls among the elderly in Siantar Martoba District, which increases with aging due to declining muscle mass and bone health. The risk is exacerbated by external factors such as non-elderly-friendly home environments and polypharmacy. Falls have serious physical impacts, such as fractures, as well as psychological consequences, including excessive fear of falling again (Post-Fall Syndrome). This study proposes a community-based educational intervention using a multifactorial approach that includes cognitive, affective, and psychomotor aspects. The expected outcomes are improved knowledge, confidence, and skills among the elderly in preventing and managing fall risks, thereby enhancing their independence and quality of life.